Extraction of Fiber from Schoenoplectus acutus Plant and Characterization of Its Properties - Alemayehu Assefa; Anmen Admas; Lijalem Haile (Advances in Materials Science and Engineering)
This work aims to extract and characterize the fibers from the Schoenoplectus acutus plant and assess their suitability for use as textile fibers. The fibers from Schoenoplectus acutus plants were extracted using alkaline extraction, water retting, and manual methods; their physical, mechanical, and chemical properties were examined. The result showed that the fiber has a tensile strength of 254.2 MPa, 302.6 MPa, and 183.4 MPa for manual, water-retted, and alkaline extraction methods, respectively. The mean values of fiber fineness were 1.32 ± 0.2 Tex for alkali-extracted fibers, 1.43 ± 0.2 Tex for water-retted fibers, and 1.64.01 ± 0.4 Tex for manually extracted fibers. The fiber contained 58% cellulose, 25.4% hemicellulose, and 13% lignin for manual extracted fibers, whereas fibers obtained from the water-retted method had 62.8% cellulose, 20.3% hemicellulose, and 10% lignin. Similarly, alkaline extracted fibers contained 60.2% cellulose, 17.8% hemicellulose, and 6.8% lignin. Generally, the extracted fiber has acceptable mechanical properties, linear density, and moisture regain, which can serve as an alternative source of textile fibers.